Reorienting Hong Kong’s Resistance
XLI, 283 p. 12 illus., 10 illus. in color.
Keywords: “This groundbreaking book gives shape to what the authors call the ‘decolonial left,’ which defines itself against the New Cold War rivalries, legacies of British colonialism, and Chinese authoritarianism, to articulate practices of protesting and living in the space of global abolitionism and internationalism from below.” – Shu-mei Shih, Edward W. Said Professor of Comparative Literature, University of California, Los Angeles, USA “This breakthrough collection of essays is provocative, sincere, and makes not only a timely contribution to Hong Kong Studies but also thoughtful challenges to all who are concerned about Hong Kong.” – Law Wing Sang, Independent Researcher in Exile This collection brings together writing from activists and scholars that examine leftist and decolonial forms of resistance that have emerged from Hong Kong’s contemporary protests. Practices such as labor unionism, police abolition, land justice struggles, and other radical expressions of self-governance may not always operate under the banners of leftism and decoloniality; yet, examining them within these frameworks uncovers historical and prefigurative sightlines that reveal their significance to Hong Kong’s future, and interlaces the city’s struggles with others around the world. Wen Liu is assistant research fellow at the Institute of Ethnology, Academia Sinica, in Taiwan. Her writing has published in journals such as American Quarterly, Feminism & Psychology, Journal of Asian American Studies, and Subjectivity. JN Chien is a Ph.D. candidate in American Studies and Ethnicity at the University of Southern California. His writing has appeared in Hong Kong Studies, The Nation, Jacobin, and Lausan. Christina Chung is a Ph.D. candidate researching the intersections of decolonial feminism and Hong Kong contemporary art at the University of Washington. Her writing has been published byAsia Art Archive, College Arts Association Reviews, and in Creating Across Cultures: Women in the Arts from China, Hong Kong, Macau and Taiwan (East Slope Publishing, 2017). Ellie Tse is a Ph.D. student in Cultural and Comparative Studies at the Department of Asian Languages & Cultures at the University of California, Los Angeles.